Clinical treatment outcomes of tuberculosis treated with the basic regimen recommended by the Brazilian National Ministry of Health using fixed-dose combination tablets in the greater metropolitan area of Goiânia, Brazil - Ferreira, Anna Carolina Galvão (Sociedade Brasileira de Pneumologia e Tisiologia, 2013)

(untitled)
OBJECTIVE: To describe the rates of cure, treatment failure, and treatment abandonment obtained with the basic regimen recommended by the Brazilian National Ministry of Health-rifampin, isoniazid, pyrazinamide, and ethambutol for two months, followed by isoniazid and rifampin for four months-involving the use of fixed-dose combination tablets (self-administered treatment), as well as to describe adverse events and their potential impact on treatment outcomes. METHODS: This was a descriptive study based on prospective data obtained from the medical records of tuberculosis patients (≥ 18 years of age) treated with the basic regimen at either of two primary health care facilities in the greater metropolitan area of Goiânia, Brazil. RESULTS: The study sample comprised 40 tuberculosis patients. The rate of cure was 67.5%, the rate of treatment abandonment was 17.5%, and there were no cases of treatment failure. Of the 40 patients in the sample, 19 (47%) reported adverse reactions, which were mild and moderate, respectively, in 87% and 13% of the cases. It was not necessary to alter the regimen or discontinue the treatment in any of the cases evaluated. CONCLUSIONS: The rate of cure obtained with the self-administered, fixed-dose combination tablet form of the new basic regimen was similar to the historical rates of cure obtained with the previous basic regimen. The rate of treatment abandonment in our sample was much higher than that considered appropriate (up to 5%).